Evaluating the acceptability and feasibility of the I Promise Program: a driving program for families with young new drivers. Issue 6 (2nd December 2005) - Votta, E; MacKay, M
Abstract : Objectives: To evaluate the acceptability and feasibility of the I Promise Program (IPP), a driving program developed for families with young new drivers (YNDs). Design, setting, and subjects: The IPP consists of a contract between parents and YNDs and a rear window decal (sticker). Program acceptability was assessed through four focus groups with 40 young new drivers (YND), two with 19 parents of YNDs, and two with 15 community members. To determine whether the program's design, materials, and procedures were working as planned, 51 families participated in a six month pilot project. Telephone and in-person interviews were conducted at months 1 and 6, respectively. Results: Participants had problems with the acceptability of the program's underlying message; content, format, and language of the materials; program cost; and proposed participant incentives. Thirty eight (75%) families completed the six month pilot. Most YNDs (75%) and parents (85%) identified the contract as a useful communication tool. Despite positive initial reactions, 50% of YNDs did not recall the content of the contract after six months. Sixty eight percent of families had problems with the decal (for example, did not stay affixed, colors faded) and only 17% of YNDs reported a lasting impact on their driving. Only 20% of families chose to continue in the program after the pilot. Conclusions: These results highlight the importance of formative and process evaluation in the development of a new prevention strategy to assess a strategy's acceptability and feasibility. In response to participants' feedback, revisions made to the program's materials and delivery model included making its two key components—the contract and decal—available online, independent of each other, and free of charge.